Estudo sobre fermentado acético a partir de kombucha - Miranda, Adriano José de (2023)
The consumer society has increased interest in understanding the processes that are linked to food production and its composition, especially regarding the presence of additives, fibers, calories and nutrients. With that, food produced by the consumer has been increasing and gaining market shelves, which leads to better acceptance for the most natural composition and beneficial to health. In this context, the kombucha drink has gained space in the market, as well as its by-product vinegar because it is produced by hand and with natural products. In this study, the fermentative potential of the kombucha culture was evaluated, proposing the production of 3 fermented acids: green tea kombucha vinegar (FAKCV), hibiscus kombucha vinegar (FAKH) and kombucha vinegar with pineapple (FAKA). The kombucha was prepared from an infusion of tea leaves and a culture of bacteria and yeast (SCOBY), 10% fermented kombucha (starter) and sweetened with 70 g/L of Apis Mellifera bee honey. The physical-chemical analyzes were performed at time zero and every 7 days until the 28th day, and at the end of the process on the 63rd day, with the exception of the alcoholic analysis that started on the 7th day until the 35th day and at the end of the process. The study contemplated exploring the production of acetic acid and the process of transformation of sugars, for this, physicochemical analyzes of pH, total acidity, ºBRIX, reducing sugars, sucrose and alcohol were carried out. The average value of acidity in acetic acid on the 28th and 63rd day for the fermented FAKCV was equal to 0.96 and 1.38% (m/V); FAKH 2.17 and 2.11% (m/V) and FAKA 1.88 and 2.05% (m/V), respectively. The pH values on the 28th day and on for FAKCV: 2.71 and 1.95; FAKH: 2.59 and 2.02 and FAKA: 2.94 and 2.15, respectively. For the soluble solids on the 63rd day, ºBRIX filtered, were for FAKCV: 4.50% (m/V); FAKH: 3.83% (m/V) and FAKA: 2% (m/V). The reducing sugar content in relation to time zero and day 63 gradually decreased and sucrose remained practically zero during fermentation. The alcohol content found at the end of the fermentation process was between 0.27% (m/V) and 0.28% (m/V) for the three samples of fermented kombucha acids. Statistical study has shown that there is an inverse relationship between the amount of sugar and acetic acid produced. It was observed that it is possible to use Apis Mellifera bee honey to replace sucrose in the production of kombucha drink or vinegar. In view of the acidity and pH obtained in the samples, the products have the potential to be consumed in food instead of commercial vinegar.